Recent progress of endoplasmic reticulum stress in the mechanism of atherosclerosis - Ni, Lin; Yang, Luqun; Lin, Yuanyuan (Frontiers in Cardiovascular Medicine, 2024)
The research progress of endoplasmic reticulum stress in atherosclerosis is a topic of great concern. The endoplasmic reticulum, a critical cellular organelle, participates in important biological processes like protein synthesis, folding, and modification. Various pathological factors may cause endoplasmic reticulum stress, and sustained or excessive endoplasmic reticulum stress can activate the unfolded protein response, ultimately resulting in apoptosis and disease. Recently, researchers have discovered that endoplasmic reticulum stress is important in the onset and advancement of atherosclerosis. Endoplasmic reticulum stress can participate in the occurrence of atherosclerosis through different pathways such as apoptosis, inflammatory response, oxidative stress, and autophagy. Therefore, we review the mechanisms of endoplasmic reticulum stress in the development of atherosclerosis and related therapeutic targets, which will contribute to a deeper understanding of the disease's pathogenesis and provide novel strategies for preventing and treating atherosclerosis.